Status and distribution of Cheer pheasant in Dhorpatan Hunting Reserve, Nepal - Subedi, Poorneshwor; Shrestha, Suresh Kumar; Baral, Hem Sagar; Garson, Peter J.; Ramesh, K. (Banko Janakari, 2017)
Abstract on PDF